Análise da implementação de técnicas de apoio à decisão para seleção de fornecedores de vidro em uma empresa de esquadrias - Ribeiro, Verônica do Pilar (2024)
In the supply chain, in the context of an aluminum frame company, glass is an important decider of the final sophistication of the product and real customer satisfaction, as it determines the acoustic and climatic quality depending on its composition. Therefore, making the best purchasing decision will directly impact the final profit obtained per work carried out. Given this scenario, the present work aims to apply the AHP (Analytic Hierarchy Process) and DEA (Data Envelopment Analysis) methods to optimize the glass supplier selection process in an aluminum frame company. The stages of the study were segmented into: data collection by the engineering and purchasing sectors, analysis of established criteria, including: price, quality, delivery, relationship, deadline and organization; application of tabulated data. Evaluations were proposed on 2 types of glass, tempered and laminated. Following the AHP technique, the criteria were distributed and compared among themselves, obtaining the percentage of importance of each of the criteria, determining supplier F03 as the most suitable for laminated glass and F04 as the most suitable for tempered glass. Using the SAGEPE website, the DEA technique was applied, considering price as input and other criteria as outputs. For the analysis, only the CRS system was evaluated, considering internal benchmarks, and oriented to the output model. For laminated glass, the most recommended suppliers are F05 and F06. With the application of AHP and DEA techniques, it was found that both complement each other. The purchasing team can be provided with new techniques for decision-making, where the AHP assists on a day-to-day basis in negotiations covering the works, and the DEA in evaluating the supplier portfolio for possible replacements or feedback, aiming for a better relationship and partnership between companies.